The rule for the sequence is S(n) = 2S(n-1) - S(n-2)
Alternative form: S(n) = S(n-1) + 3
Step-by-step explanation:
In this problem, we know the first two terms of the sequence:
S(1) = 2
S(2) = 5
We are told that each term after the second is created by subtracting the term before the previous term from twice the previous term. In other words, if we call:
S(n) the current term
S(n-1) the previous term
S(n-2) the term before the previous term
This statement translates into the following sequence:
S(n) = 2S(n-1) - S(n-2)
Because we are subtracting the term before the previous term, S(n-2), from twice the previous term, 2S(n-1).
We can apply now the rule to find the first few terms of the sequence after S(1) and S(2):
![S(3) = 2S(2) - S(1) = 2(5)-2=10-2 = 8](https://tex.z-dn.net/?f=S%283%29%20%3D%202S%282%29%20-%20S%281%29%20%3D%202%285%29-2%3D10-2%20%3D%208)
![S(4) = 2S(3) - S(2) = 2(8)-5=16-5 = 11](https://tex.z-dn.net/?f=S%284%29%20%3D%202S%283%29%20-%20S%282%29%20%3D%202%288%29-5%3D16-5%20%3D%2011)
![S(5) = 2S(4) - S(3) = 2(11)-8=22-8 = 14](https://tex.z-dn.net/?f=S%285%29%20%3D%202S%284%29%20-%20S%283%29%20%3D%202%2811%29-8%3D22-8%20%3D%2014)
We notice also that each term of the sequence is just equal to the previous term plus 3, so the sequence can also be written as
S(n) = S(n-1) + 3
Learn more about sequences:
brainly.com/question/1522572
brainly.com/question/3280369
#LearnwithBrainly